Molecular and Microbial Detections of Streptococcus mutans and Lactobacilli in Dental Caries: An Experimental Study on Iranian Children Aged 5–9 - Marzieh Danaei; Milad Mollaali; Vida Fakharmohialdini; Hamidreza Poureslami; Fatemeh Sadat Sajadi; Elham Farokh Gisour; Fatemeh Jahanimoghadam; Aida Gholampour; Mehrnaz Foroudisefat; Arezoo Mirshekari; Raziyeh Shojaeipour (Clinical and Experimental Dental Research)
ABSTRACT Objectives Lactobacilli and Streptococcus mutans are stigmatized as cariogenic bacteria, but few studies have simultaneously examined the quantitative and qualitative aspects of lactobacilli and S. mutans in childhood dental caries. Therefore, this study aimed to detect the presence of S. mutans and lactobacilli in dental caries using Snyder's test, colony counting, and PCR in the primary teeth of Iranian children with dental caries. Material and Methods A cross‐sectional study was conducted in Kerman, Iran, from March to Jun 2024. After dental examinations, 120 eligible children aged 5–9 were chosen using simple random sampling and classified into four groups based on their decayed, missing, and filled (primary) teeth (dmft) index: Group 1 (dmft = 0), Group 2 (dmft = 4–6), Group 3 (dmft = 7–9), and Group 4 (dmft = 10–13). The salivary levels of lactobacilli and S. mutans were calculated using colony counting (CFU/ml). Moreover, Snyder's test was applied to evaluate caries activity. PCR was also performed for molecular detection of lactobacilli (16S rRNA gene) and S. mutans (gftB gene). Lastly, the association between bacterial counting, molecular findings, and Snyder's test was estimated through statistical methods using SPSS 27. Results Significant differences were found between the age and the PCR results of lactobacilli and S. mutans among all dmft Groups (p < 0.05). Moreover, positive significant correlations were observed between the counts of lactobacilli and S. mutans in dmft Group 1 compared to other dmft Groups (p < 0.05). Furthermore, the counts of these two bacteria differed significantly in Snyder's test (p < 0.05). However, Snyder's test differed significantly from the S. mutans PCR (p < 0.05), but not from the lactobacilli PCR (p > 0.05). Conclusions The results of the study could potentially be considered a promising and cost‐effective screening program to identify children who are susceptible to dental caries.